Photochemical reaction of Cp*Ir(CO)2 with C6F5X (X = CN, F) : formation of diiridium(II) complexes - Ganguly, Rakesh (2014)
Visible light irradiation of Cp*Ir(CO)2 (1) in pentafluorobenzontrile resulted in the formation of the two isomeric diiridium(II) complexes [Cp*Ir(μ-CO)(C6F4CN)]2 (3) and [Cp*Ir(CO)(C6F4CN)]2 (4), while the analogous reaction of 1 in hexafluorobenzene to give [Cp*Ir(μ-CO)(C6F5)]2 (3a) required UV irradiation. Complex 4 isomerizes to 3 under visible light irradiation. A reaction pathway to 4 involving aromatic nucleophilic substitution has been proposed on the basis of experimental and computational data. The isomerization of 4 to 3 is believed to proceed via a radical species resulting from homolytic fission of the Ir−Ir bond.